THE EFFECT OF GARLIC (Allium sativum Linn) SKIN EXTRACT ON NITRIC OXIDE AND TNF-α LEVELS IN ACUTE BACTERIAL SINUSITIS - Renny Swasti Wijayanti; Shelly Tjahyadewi; Isnawati Budi Panuntun; Afifah Fairuz Zahira (Syntax Corporation Indonesia, 2023)
Background : During the course of the disease, acute bacterial rhinosinusitis produces several inflammatory mediators such as levels of Nitric Oxide (NO) and TNF-α which cause changes in cell and tissue structure. Currently, there is no research on the effect of garlic skin extract on nitric oxide and TNF-α levels in acute bacterial rhinosinusitis. Methods : This post-test only control group design experimental study used 28 male white rats of the Sprague Dawley strain which were divided into 4 groups, namely a control group, a group of rats with bacterial acute sinusitis without treatment, a group of rats with acute bacterial sinusitis with amoxicillin antibiotics and anti-inflammatory prednisolone, and a group Bacterial acute sinusitis rats with the antibiotic amoxicillin and garlic skin extract. The study was conducted for 21 days, on the 22nd day blood samples were taken from the orbital vein and measured levels of NO and TNF- α using an ELISA reader. Results : The mean levels of TNF- α in the first to fourth groups respectively were 6.13 ± 0.31 ng/mL; 17.68 ± 4.29 ng/mL ; 6.65 ± 0.43 ng/mL ; 6.86 ± 0.26 ng/mL. The analysis showed that the data were normally distributed and not homogeneous. The One Way ANOVA test showed that there were at least two groups of data that had a significant mean difference (p < 0.05). The results of the LSD Post Hoc Test showed a significant difference between group K against P1, P2 and P3, group P1 against P2 and P3. And there was no significant difference between the P2 and P3 groups (p < 0.05). Conclusion : The administration of garlic skin extract (Allium sativum Linn) affected the levels of NO and TNF- in rats with acute bacterial sinusitis induced by Staphylococcus aureus.